A 22:1 Compression Ratio Ammonia-Hydrogen HCCI Engine: Combustion, Load, and Emission Performances - Pochet, Maxime; Jeanmart, Hervé; Contino, Francesco (Frontiers in Mechanical Engineering, 2020)
The interest in ammonia as a high-density hydrogen carrier for long-term electricity storage is growing. A clean and efficient Combined Heat and Power (CHP) system is envisioned for power production from stored ammonia, to which Homogeneous-Charge Compression-Ignition (HCCI) engines are promising. Although recent preliminary studies showed a high equivalence ratio potential for ammonia HCCI engines, its resistance to auto-ignition forces the use of high intake temperatures, which limits the (still unknown) ammonia-HCCI power density. Moreover, the feasibility of clean and highly efficient ammonia combustion has not been demonstrated. To give a first complete insight on these various aspects, an HCCI test bench has been modified to ammonia-hydrogen operation through the use of a 22:1 effective compression ratio. A cartography of the ammonia-hydrogen load range, related efficiencies and emissions is obtained following the impact of the ammonia fuel blending ratio (from 0 to 94%), equivalence ratio (from 0.1 to 0.6), intake temperature (from 50 to 240°C) and Exhaust Gas Recirculation. Thanks to a reduced combustion intensity, ammonia allows a 50% IMEP increase compared to neat hydrogen, while maintaining equivalent combustion efficiencies. Neat hydrogen performances were not impacted from the high compression ratio. Fuel-NOX emissions have been observed, and linearly increasing with the ammonia flow rate up to 6,000 ppm, although the EGR led to a three-fold reduction of those. Still EGR negatively impacted NO2 and unburned emissions. Below combustion temperatures of 1,400 K the production of N2O is suspected and 1,800 K are needed to ensure complete bulk ammonia combustion. Finally, the trade-off for the ideal ammonia-hydrogen blending ratio is discussed. As perspectives, extensive work is needed on fuel-NOX primary reduction measures and after-treatment ways. Regarding primary measures, this work suggests that boosted conditions with maximized stroke-to-bore ratios should be aimed at, to allow higher EGR rates at maintained combustion temperatures.